They can do it. Positive Authoritarianism in Poland and Hungary - Wagner, Franziska; Enyedi, Zsolt (Frontiers in Political Science, 2024)
It is often assumed that right-wing authoritarian and populist parties appeal primarily to negative feelings such as frustration, fear or alienation, and that positive sentiments appear in their discourse mostly in the form of nostalgia. Our hypothesis is that this description fails to apply to leaders in power. This article employs a mixed-methods approach, using a novel dataset of Viktor Orbán’s (Fidesz - Hungary) and Jarosław Kaczyński’s (PiS - Poland) speeches. After grouping positive sentences, a structural topic model identifies central topics, while the qualitative part describes and contextualizes the nature of the detected positive messages. Our analysis reveals that Orbán and Kaczyński incorporate various types of positive sentiments, such as optimism, pride, and efficacy, into their discourse. Contrary to popular belief, they dedicate considerable attention to discussing the future and utilize various rhetorical devices to convey positive messages. These messages are intrinsically interwoven with the leaders’ visions of past and future, offering insights into the underlying framework of their fundamentally conflict-centered and illiberal worldview. This study challenges the notion that right-wing authoritarian politics rely solely on “politics of fear”. Instead, it suggests that such leaders employ positive affective appeals as a form of emotional governance.